Sodium (23Na) MRI detects elevated muscular sodium concentration in Duchenne muscular dystrophy - Weber, Marc-André; Nagel, A. M.; Jurkat-Rott, K.; Lehmann-Horn, F. (Neurology, 2011)
Objective: In boys with Duchenne muscular dystrophy (DMD), 1H MRI suggested muscular edema before fatty degeneration. Using specific 23Na MRI sequences, we tested the hypothesis that the edema is caused by an osmotic effect due to increased myoplasmic Na+ content rather than inflammation that would lead to extracellular edema. - Methods: Eleven patients with DMD (mean age, 10 ± 5 years) and 16 healthy volunteers of similar age were examined on a 3-T system with 1H MRI and 23Na density-adapted 3-dimensional radial MRI sequences. The muscle edema was quantified on short-tau inversion recovery images using background noise as reference. Fatty degeneration was quantified on T1-weighted images using subcutaneous fat as reference. Na+ was quantified by a muscular tissue sodium concentration (TSC) sequence. A novel inversion recovery (IR) sequence allowed us to determine mainly the myoplasmic Na+ by suppression of the extracellular 23Na signal from vasogenic edema. A reference tube containing 51.3 mmol/L Na+ with agarose gel was used for standardization. - Results: The normalized muscular signal intensity of 23Na as assessed by the IR sequence was significantly higher for patients with DMD than for volunteers. TSC was markedly increased at 38.4 ± 6.8 mmol/L in patients with DMD compared with 25.4 ± 2.1 mmol/L in volunteers. The muscular edema-like changes were much more prominent in patients with DMD than in volunteers. In addition, the muscular fat content was significantly higher in patients with DMD than in volunteers. - Conclusions: The elevated myoplasmic Na+ concentration in DMD is osmotically relevant and causes a mainly intracellular muscle edema that contributes to the pathogenesis of DMD.